Analisis Pemanfaatan Sumber Daya Alam dalam Meningkatkan Perekonomian di Kota Medan - Surya Alfi Nurrahma; Muhammad Yahfiz (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Medan is the third largest city in Indonesia, after Jakarta and Surabaya, and is located in thenorthern part of the island of Sumatra, specifically in the province of North Sumatra. Natural resources in theMedan city area, when combined with dependable human resources, strengthened by the application ofscience and technology, and supported by appropriate utilization and management policies, can be asignificant source of development capital to improve the community's economy. The goal of this study is tolook at the accomplishments of various programs and activities aimed at improving the quality of naturalresources in the city of Medan's economy. This study's method is a qualitative research method with a type ofliterature review research sourced from BPS, Journals, and other books. The findings of this study indicatethat the utilization of natural resources in the Fisherman's Village and the policies or strategies establishedby the government are still not being carried out optimally, as evidenced by the surrounding community'slower economic level, as indicated by the income level of traditional fishermen in the research area, theresults of which are average. - average Rp. 1,429,551. and the use of natural resources has had little impacton the city of Medan's economic growth.